2014
DOI: 10.1002/ptr.5251
|View full text |Cite
|
Sign up to set email alerts
|

The Immunostimulating Role of Lichen Polysaccharides: A Review

Abstract: The immune system has capacity to suppress the development or progression of various malignancies including cancer. Research on the immunomodulating properties of polysaccharides obtained from plants, microorganisms, marine organisms, and fungi is growing rapidly. Among the various potential sources, lichens, symbiotic systems involving a fungus and an alga and/or a cyanobacterium, show promise as a potential source of immunomodulating compounds. It is well known that lichens produce an abundance of structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 61 publications
(76 reference statements)
0
56
0
Order By: Relevance
“…Immunostimulants are of great interest in health care and have become one of the most active areas of applied medical research. Immunostimulants, which can promote and induce a strong defence response in the host, include polysaccharides, hormones, vitamins, different components of bacteria, biologically active materials, Chinese herbs and synthetic drugs (Mohapatra, Chakraborty, Kumar, DeBoeck & Mohanta ; Buchmann ; Kasahara & Sutoh ; Song, Beck, Kim, Park, Kim, Kim & Ringø ; Shrestha, St Clair & O’ Neill ; Masahiro ). Immunostimulants are critical in eliciting immune responses capable of providing complete protection against certain pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Immunostimulants are of great interest in health care and have become one of the most active areas of applied medical research. Immunostimulants, which can promote and induce a strong defence response in the host, include polysaccharides, hormones, vitamins, different components of bacteria, biologically active materials, Chinese herbs and synthetic drugs (Mohapatra, Chakraborty, Kumar, DeBoeck & Mohanta ; Buchmann ; Kasahara & Sutoh ; Song, Beck, Kim, Park, Kim, Kim & Ringø ; Shrestha, St Clair & O’ Neill ; Masahiro ). Immunostimulants are critical in eliciting immune responses capable of providing complete protection against certain pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The published studies have shown that some lichen polysaccharides demonstrate the anti-inflammatory effect due to alteration of the production levels of various cytokines by macrophages [19]. Omarsdottir et al [20] examined the influence the lichen polysaccharides (Pc-1, Pc-2, Pc-3 and Pc-4, isolated from Peltigera canina) on cytokine production by rat peritoneal macrophages and rat spleen cells.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…It has been found that some lichens have antitumor activity through components such as polysaccharide, glucan and glycoprotein. Antimicrobial activities against different bacterial species were identified in lichens where many antibiotic substances were detected (Shrestha and St. Clair, 2013;Shrestha et al, 2015).…”
Section: Different Usage Areas Of Lichensmentioning
confidence: 99%